Evaluation of intraoperative cone beam computed tomography and optical drill tracking in temporal bone surgery. (5th August 2013) - Erovic, Boban M.; Daly, Michael J.; Chan, Harley H. L.; James, Adrian L.; Papsin, Blake C.; Pothier, David D.; Dixon, Ben; Irish, Jonathan C.
Abstract : Objectives/Hypothesis: A prototype system for intraoperative cone beam computed tomography (CBCT) imaging has been developed and augmented with real time optical tracking of a surgical drill. We hypothesize that this system provides sufficient accuracy for guidance of temporal bone surgery. Study Design: Basic research. Methods: Measurements of drill localization accuracy using CBCT imaging were obtained with a custom three‐dimensional calibration object. Integrated CBCT imaging and drill tracking were prospectively evaluated on 12 cadaver temporal bones. Six inexperienced and six experienced surgeons conducted four surgical tasks: cortical mastoidectomy, posterior tympanotomy, cochleostomy, and a translabyrinthine approach to the internal auditory canal. Questionnaires provided expert feedback on tracking accuracy and system usability. Results: Target registration error measurements of drill tracking accuracy and precision yielded a mean of 0.76 mm, a maximum of 1.30 mm, and a standard deviation of 0.21 mm. Anatomical landmark identification tasks (e.g., facial nerve, incus, semicircular canals, cochlea) provided additional validation of system accuracy. The usability and utility of the guidance system were positively rated by both groups of surgeons, with further modifications underway to improve tracking line of sight and registration workflow. Experienced but in particular inexperienced surgeons indicated significant benefits in cases involving extensive disease, abnormal anatomy, and loss of anatomical landmarks. Conclusions: The integration of intraoperative CBCT imaging with optical tracking provides sufficient accuracy to localize anatomical structures within the temporal bone using an otological drill. Future studies will explore the role of this technology in complex oncological resections, in surgery for congenital anomalies, and as a tool for teaching. Level of Evidence: 4. Laryngoscope, 123:2823–2828, 2013